Amalan budaya masyarakat Tamil dalam antologi Akananuru / Arunasalam A/L Sereenevasan - Sereenevasan, Arunasalam (2015)

(untitled)
Literature demonstrates the life of an ethnic group in a period of time. The style of life is described in an open and hidden manner in various literary forms. This thesis entitled, “Culture Practices of Tamil Society In Akananuru Anthology”, is an exposition about the traits and lifestyle of the Tamils during the cangam period. This study is done on the Akananuru anthology, a collection of 400 poems. The Qualitative Method which is based on library research was used as the main appraoch to explain the cultural and social issues of the Tamilians at the cangam period. To support this dissertation, facts and information were obtained from books, academic research articles and journals. The objective of this study is to identify the moral values of the Tamil civilization at the cangam period as portrayed in the Akananuru anthology. Moreover it also studies the traits of the Tamil society which are found in the Akananuru anthology. The findings of this study is presented in seven main chapters. The first chapter of the research begins with an introduction about the Tamil language and Tamil literature in the Akananuru anthology. This is followed with the literature review, research objective, significance of research, research methodology, research scope, theory and the chaptering of the thesis. Chapter two discusses the belief system, worshiping of deities and cultural practices of the Tamils during the cangam period such as offering prayers to Lord Muruga (Veriyaddam) and Goddes Kottravai (Kottravai valipaadu). Besides that cultural practices and daily rituals such as wedding ceremonies, keeping track of the day and time, erecting monuments, astrology, choosing a community representative, and organizing a warehouse are also discussed in this chapter. The community life of the Tamils during the cangam period are enriched with affection. The bonding and affection among humans and also compassion towards the animals are discussed in chapter three. Chapter four presents on various daily practises such as food consumption, occupation and transportation. Dietary pratices such as cooked porridge and sour rice and otnerpractices pertaining to occupations involving business, agriculture and fishing were detailed in this chapter. Chapter five discusses the traditon of ornamentation. The Tamils were actively involved in beautifying themselves like hair styling, wearing necklaces, earrings, applying eye shadow and fragnances. Other than this wearing saree and slippers was discussed. Chapter six discusses games and art activities which were practised by the Tamil society. They participated in games such as playing ball, swing, and building sand statues. Art activities such as sketching and statue carving are also included in this chapter. Chapter seven summarizes the research. In conclusion the analysis proves the existence of cultural practises which upholds virtuous values and norms.